HUBUNGAN STATUS GIZI PADA IBU HAMIL TERHADAP KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS IMOGIRI II BANTU - Wilda Fadhilatusafitri; Nurul Kurniati (Journal of Innovation Research and Knowledge, 2025)
Stunting is a condition of failure to thrive in children due to chronic malnutrition characterized by below-standard height for age, and has an impact on the cognitive development and learning ability of children in the future. The high prevalence of stunting in Indonesia is still a serious public health problem, where one of the main factors that play a role is the nutritional status of the mother during pregnancy. This study aims to analyze the relationship between the nutritional status of pregnant women and the incidence of stunting in toddlers. This study used an analytic survey method with a cross-sectional approach. The study sample amounted to 74 respondents selected by purposive sampling technique, and data were collected through medical records to see the nutritional status of pregnant women and the incidence of stunting in toddlers. Data analysis was performed using the Chi-Square test with a significance level of α < 0.05. The results showed that most pregnant women had poor nutritional status (55.4%), followed by good nutritional status (28.4%) and more (16.2%). The incidence of stunting in toddlers reached 55.4%, and the results of statistical tests showed a significant relationship between the nutritional status of pregnant women and the incidence of stunting in toddlers (p-value=0.000). All mothers with poor nutritional status had toddlers who were stunted (100%), while mothers with good and more nutritional status had toddlers who were not stunted (100%). In conclusion, the nutritional status of mothers during pregnancy is an important determinant in the incidence of stunting in toddlers in the working area of Puskesmas Imogiri II Bantul